Home care nursing for persons with dementia from a family caregivers' point of view: Predictors of utilisation in a rural setting in Austria. (7th May 2021) - Krutter, Simon; Schaffler‐Schaden, Dagmar; Eßl‐Maurer, Roland; Seymer, Alexander; Osterbrink, Juergen; Flamm, Maria
Abstract: The service utilisation of persons with dementia (PwD) and their caregivers is subject to lively debate. The reasons for non‐utilisation are manifold and heterogeneous. Conceptual models and explanatory frameworks may help identify predictors of the usage of health services. Literature examining the utilisation of home care services for PwD is scarce. This study explored predictors of home care nursing utilisation of PwD and their informal caregivers in a rural setting, according to the Andersen Behavioural Model of Health Care Use. A mixed‐methods study was conducted in a rural area of Austria. In using non‐random multistage sampling, anonymous questionnaires were distributed to collect data on family caregivers of PwD. Data were analysed using sequential binary logistic regression to characterise home care service users. To reflect the complexity of the Andersen model, a regression tree model was used. In total, 107 family caregivers completed the survey. Predisposing factors for home care nursing utilisation were higher age of the caregiver, female gender of PwD and kinship of the PwD and caregiver. Disruptive behaviour and independence in activities of daily living of PwD were associated with need factors for service use. According to the Andersen model, the predisposing and need factors contributed most to the explanation of home care nursing utilisation. The enabling factors employment, education and income tend to predict service use. Our findings indicate that higher age of the family caregiver and female gender of PwD are the main predictors for utilisation of home care nursing in a rural setting. To improve utilisation, the advantages of professional care services should be promoted, and the awareness about the variety of services available should be increased. To ensure a better understanding of the barriers to accessing home care, PwD should more often be included in healthcare service research.